A novel upconversion luminescence derived photoelectrochemical immunoassay: ultrasensitive detection to alpha-fetoprotein. Issue 42 (20th October 2017) - Chen, Xu; Xu, Wen; Jiang, Yandong; Pan, Gencai; Zhou, Donglei; Zhu, Jinyang; Wang, He; Chen, Cong; Li, Dongyu; Song, Hongwei
Abstract : A upconversion luminescence derived photoelectrochemical Immunoassay for ultrasensitive detection to Alpha-fetoprotein under near infrared lights illumination. Abstract : Fabrication of near-infrared light-triggered photoelectrochemical (PEC) sensors based on the upconversion nanophosphors (UCNPs) is a novel approach, which exhibits the advantages of low background signal and non-damage to the biological substance as well as high sensitivity and improved electric detection in PEC sensors. Herein we demonstrate the preparation of novel and high-quality ZnO inverse opal photonic crystals (IOPCs)/Ag/NaYF4 :Yb, Tm hybrid films by different advanced film techniques, including colloidal self-assembling, vapor phase deposition and pulsed laser deposition and its application to sensitive detection of alpha-fetoprotein (AFP). In the complex device, ZnO IOPCs and surface plasmon resonance (SPR) of silver had ability to largely enhance local excitation electromagnetic field of NaYF4 :Yb, Tm, resulting in efficient near-infrared to visible/ultraviolet upconversion luminescence (UCL). The ultraviolet light emitted by NaYF4 :Yb, Tm could b further reabsorbed by ZnO, generating PEC responses. Furthermore, because of the high specific surface area of ZnO IOPCs and the conductivity of Ag films, ZnO IOPCs/Ag/NaYF4 :Yb, Tm hybrid films based near-infrared light-triggered PEC sensors showed ultrasensitive detection of AFP with a linear range from 0.05 ng mL −1 to 100 ng mL −1 and a low detection limit of ∼0.04 ng mL −1 (40 pg mL −1 ). Such an advanced device also shows promise in detection of other cancer markers in clinical and biological analysis.